2017
DOI: 10.3389/fphar.2017.00704
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Exposure to Tributyltin Blocks Leydig Cell Regeneration in the Adult Rat Testis

Abstract: Background: Tributyltin (TBT) is widely used as an antifouling agent that may cause reproductive toxicity. The mechanism of TBT on Leydig cell development is still unknown. The objective of the present study was to investigate whether a brief exposure to low doses of TBT permanently affects Leydig cell development and to clarify the underlying mechanism.Methods: Adult male Sprague Dawley rats were randomly assigned into four groups and gavaged normal saline (control), 0.1, 1.0, or 10.0 mg/kg/day TBT for a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Leydig cells in the testis interstitial compartment contribute 95–99% of circulatory testosterone ( Wu et al, 2017 ). Testosterone biosynthesis is catalyzed by SCARB1, STAR, CYP11A1, 3β-HSD, CYP17A1, and 17β-HSD3 ( Wang et al, 2011 ), which gets promoted when LH binds to LHCGR on its surface ( Melsert et al, 1991 ; Foster, 1996 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leydig cells in the testis interstitial compartment contribute 95–99% of circulatory testosterone ( Wu et al, 2017 ). Testosterone biosynthesis is catalyzed by SCARB1, STAR, CYP11A1, 3β-HSD, CYP17A1, and 17β-HSD3 ( Wang et al, 2011 ), which gets promoted when LH binds to LHCGR on its surface ( Melsert et al, 1991 ; Foster, 1996 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the various toxicities of DBTCl, it has been reported to suppress testosterone production induced by tropic stimulation, thereby demonstrating its negative effects on Leydig cells ( Nakajima et al, 2005 ; Brown et al, 2017 ; Furukawa et al, 2017 ; Milton et al, 2017 ; Zhang et al, 2018 ). Another organotin, tributyltin chloride (TBT), has been demonstrated to block Leydig cell developmental regeneration in the adult rat testis ( Wu et al, 2017 ); therefore it is worth wondering whether DBTCl has the similar effects as both TBT and DBTCl are organotins. Thus, the present study was conducted to investigate the effects of DBTCl on Leydig cell developmental regeneration, using the EDS-induced rat Leydig cell developmental regeneration model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that EDS could selectively ablate all the differentiated LCs in the rat testis (Sharpe et al, 1990;Morris et al, 1997;Wu et al, 2017). The blank control (not contain DMSO), 0 mg/mL EDS, and 1.0 mg/mL EDS was added to the culture solution (Yu et al, 2017).…”
Section: Ethane Dimethane Sulfonate (Eds) Treatmentmentioning
confidence: 99%